Coronavirus Disease 2019 (COVID-19) Outbreak: A Pandemic and Public Health Emergency - Aishwarya Pandey, Rasanpreet Kaur, Sunil Kumar, Sudarshan Singh Lakhawat, Vikram Kumar (International Journal of Advanced Science and Technology, 2020)
The Covid-19 is the biggest viral outbreak which first originated in wuhan province of China and now became the biggest pandemic of this Centuary. The symptoms of disease includes loss of taste, loss of smell, dry cough, fever which may progress later into pneumonia due to inflammation of lower respiratory tract. The virus tends to differ in severity of infection with majority 80 percent of infected individuals showing mild or no symptoms at all but those which are elderly or ones suffering from co morbid disorders such as diabetes, cancer, HIV etc. are at high risk of developing pneumonia and severe acute respiratory distress. Such patients require immediate hospitalization and intubation to support oxygen saturation in blood along with using ventilators. The studies shows that there are striking similarity between the genomes of SARS Cov-I and Covid-19 virus but Covid-19 presents with exceptionally high contagious nature which is a great concern and therefore currently most of the countries are concentrating  only on the procedures to stop the spread of virus by adopting  stringent lockdown measures. In current review we focus upon the intensity, pathogenesis, countries affected and preventive vs clinical measures taken to contain and eradicate the disease. Currently no effective vaccine nor accurate treatment is available to stop the corona virus spread but studies showed that combined antiviral therapy against Covid-19 using anti HIV and anti SARS Cov-I drugs along with antimalarial medication provides acute relief in terms of respiratory symptoms and decreases rate of morbidity. Keywords: Covid-19, SARS CoV, MERS-CoV, Corona virus, Middle East Respiratory Syndrome, Severe Acute Respiratory Syndrome.